Compatibilidad de injerto por yemas en cuatro variedades de cítricos utilizando como patrón la mandarina Cleopatra (Citrus reshni), en la zona Babahoyo. - Rodriguez Troya, Lizbeth Samantha (2025)
The Cleopatra mandarin (Citrus reshni) draws attention as an alternative in agriculture as a rootstock because this rootstock is resistant to diseases, pests and has an excellent adaptation to the different grafted varieties. This research was carried out at the Technical University of Babahoyo of Agricultural Resources, in the nursery. The objective that was met was to evaluate the compatibility of the bud grafts in four varieties of citrus. The experimental design that was used is completely random with 4 treatments with 5 repetitions, with the Tukey test at 95% probability. The variables used were percentage of take, number of leaves, diameter of the shoot stem, shoot height, leaf area, number of shoots, shoot vigor at 60, 90, 120 days. These data helped us determine the compatibility between the Cleopatra mandarin rootstock with the varieties used: tangelo orange, lime orange, blood orange, chonera mandarin. The results obtained at 60, 90 and 120 days the percentage of take was 100% in the 4 treatments, the Chonera mandarin variety at 120 days had the highest shoot height with 60.40 cm, the number of shoots with 4.87 and number of leaves with 62.8 this mandarin variety stands out in these variables. The largest diameter of the shoot stem at 120 days was from the T1 tangelo orange treatment with 5.08 mm, in terms of shoot vigor according to the rating and interpretation scale at 120 days the 4 citrus treatments had a percentage of 4 which is the highest number on the scale. It was concluded that the 4 citrus varieties grafted onto the Cleopatra mandarin rootstock had an excellent percentage of take and vigor. The T4 Chonera mandarin stood out in shoot height, number of shoots and number of leaves on the shoot at 120 days with 60.40 cm shoot height, 4.87 number of shoots and 62.8 leaves, demonstrating its notable compatibility with the Cleopatra mandarin pattern. In shoot stem diameter at 120 days, the T1 tangelo orange treatment proved to be the variety that stood out the most. The treatment with the largest leaf area was the T2 lime orange treatment with 50 cm2, this variety stood out as the treatment with the best leaf area